IMPLEMENTASI PSAK NO. 45 DALAM PELAPORAN KEUANGAN ENTITAS NIRLABA BERSTATUS BADAN LAYANAN UMUM - Mutmainah, Siti Nurlaela dan (Paradigma, 2014)
The target of the research is to implementation of organizational financial  statement of the organization (Balai Besar Kesehatan Paru Masyarakat). Implementation was conducted to find out whether the presentation of Balai Besar Kesehatan Paru Masyarakat financial statement is in accordance with Statement of Standard Financial Accounting (PSAK) Number 45. Result of the research indicated that  Balai Besar Kesehatan Paru Masyarakat Surakarta has presented financial statement matching PSAK No.45, that can be seen in its financial statement component consisting of : financial position report, activity report, cash flow statement, and note to the financial statement.Analysis result in this research indicated that there is some revision in the financial statement. Firstly, the presentation concerning the resource which the BBKPM Surakarta has, like : unattached net asset, transient tied, and tied permanent which are grouped into equity which mirror in financial position report. Equity at  profit organization/company represents owner equity which consists of capital stoock and retained earning, while at the non-profit organization like BBKPM Surakarta, its ownership is not based on the capital stock and retained earning. Secondly, BBKPM Surakarta had better consider assessment and abolishment of stock.  Keyword : applying PSAK No. 45, presentation of financial statement BLU